Administrative empowerment and its relationship to job performance in special education centres in Karak Governorate: the employee perspective - W.A.M. Al-Momani; A.M.B. Melhem (Образование и наука)
Introduction. Administrative empowerment in special education centres is of great interest because it involves changing approaches to organisational management in the system of special (correctional) education. This, in turn, impacts the success and sustainability of the activities of such centres. Aim. The present research aimed to quantify the extent to which employees in special education centres felt empowered by their supervisors and how that empowerment correlated with their job productivity. Methodology and research methods. To achieve the research objective, the authors utilised the correlational survey method and created two questionnaires. The first questionnaire examined the administrative empowerment transferred to staff members. The second questionnaire was administered to assess the employees’ job performance following the implementation of administrative empowerment. 112 employees of special education centres participated in the study voluntarily. Results. The results of the study showed a positive correlation between administrative empowerment and the growth of labour productivity in the centre. At the same time, there were differences in job performance based on variables such as gender, years of experience, academic qualifications, and attendance at training courses. Scientific novelty. The study identified key factors that can enhance job performance in special education centres to support students with special needs. Practical significance. The research findings will be of interest to academics, scholars, and educators working in the field of special education.